IMPLEMENTASI KURIKULUM K13 PADA PEMBELAJARAN PJOK DI MIN 1 BOJONEGORO - Dwi Cahyono, Febryan; Mujahidin, Ali; Bakri (Penerbit Pendidikan Olahraga STKIP PGRI Bangkalan, 2019)
Penelitian ini bertujuan untuk mengetahui hasilimplementasi progam kurikulum k13 yang dilakukan di Madrasah Ibtidaiyah Negeri 1 Bojonegoro yang memberi perubahan jam pembelajaran pendidikan jasmani, olahraga dan kesehatan. Jenis penelitian ini adalah penelitian action research dengan mengamati dan mencari data hasil pembelajaran ujian nasional dan ujian keterampilan/praktik siswa. Teknik analisis menggunakan analisis deskriptif, korelasi dan regresi. Dari hasil penelitian yang dilakukan didapatkan bahwa terdapat hubungan yang kuat antara prestasi akademik siswa dengan kemampuan biomotor yaitu dengan nilai korelasi sebesar0.604. kemudiandari hasil uji analisis regresi menunjukkan bahwa prestasi akademik siswa 36.5% dipengaruhi oleh kemampuan biomotor, sedangkan sisanya dipengaruhi oleh faktor lainnya. Berdasarkan hasil penelitian dapat disimpulkan bahwa kebijakan penggunaan kurikulum k13 dalam program penambahan jam pada mata pelajaran pendidikan jasmani, olahraga dan kesehatan sudah sesuai dengan usaha madrasahuntuk meningkatkan prestasi akademik dan kemampuan biomotor siswa. This study aims to determine the results of the implementation of the K13 curriculum program conducted at the 1 st Bojonegoro State Madrasah Ibtidaiyah which provides changes in hours of learning in physical education, sports and health. This type of research is a survey research by observing and looking for data on the results of national examination learning and student skills / practice tests. The analysis technique uses descriptive analysis, correlation and regression. From the results of research conducted found that the academic achievement of students has an average value of 73.0, which is included in the category of B grades. While the ability of biomotor students included in the category of B grades is also due to having an average value of 82.7. From the results of the correlation test there is a strong relationship between students' academic achievement and biomotor abilities with a correlation value of 0.604. Furthermore, the results of the regression analysis test showed that 36.5% of students' academic achievement was influenced by biomotor abilities, while the rest was influenced by other factors. Based on the results of the research that has been done, it can be concluded that the implementation of the K13 curriculum influences the academic value and good sports skills of students and in the implementation of four hours of physical education and sports learning is able to influence the students' academic results.